The effect of reiki on fatigue and sleep quality in individuals with multiple sclerosis: a randomised controlled study - Turan, Gulcan Bahcecioglu; Ozer, Zulfunaz; Arikan, Elanur (Elsevier Science Inc, 2024)
The aim of the study is to investigate the effect of the application of Reiki on fatigue and sleep quality in people with MS. The study is a randomised controlled study. A total of 60 people (control group = 30, intervention group = 30) participated in this study. Personal Information Form, Piper Fatigue Scale (PFS) and Pittsburg Sleep Quality Index (PSQI) were used to collect data. It was found that the PFS and PSQI total and subcomponent scores of the intervention group decreased after Reiki compared to the control group and this was statistically significant (p < 0.05). The study showed that Reiki was significantly effective in improving fatigue and sleep quality in people with MS. As Reiki is a simple, inexpensive and accessible method, it was suggested that its use in the management of MS should be encouraged and maintained in nursing practice.
Keywords: Fatigue; Multiple sclerosis; Nursing; Reiki; Sleep quality